Character Education’s Dialectics Based on Art and Culture in the Approach of Cultural Studies - Ediwar, Ediwar; Elizar, Elizar; Wahyuni, Wahida; Admiral, Admiral; Syofia, Ninon; Nurmalena, Nurmalena (International Journal Labs, 2023)
Background: Dialectics of character education based on local culture is conducted through the approach of cultural studies in order to comprehend meanings resulted symbolically from the phenomena of local culture. The process of character education based on local culture is a process that gives an individual the ability to give meaning toward his/herself and his/her environment. Aim: The researchers would like to analyze character education’s dialectics based on art and culture in the approach of cultural studies. Method: Literature studies related to character education studies based on local culture in Minangkabau were carried out through written and oral sources or primary and secondary sources. Qualitative methods with a multidisciplinary approach were used. Field data collection was managed in an 'etic' and 'emic' manner. The data were then analyzed using Miles and Huberman techniques. Findings: The attitude of West Sumatera government that launches the program of